An intelligent system for document-based banking processes - Doğuç, Özge (Kahramanmaras Sutcu Imam University, 2022)
Business process automation has been helping companies by eliminating mundane and repetitive tasks. Automation tools have been used in many sectors, providing high full-time employee (FTE) savings and low error rates to the companies. Banks have been utilizing the automation tools for core banking and branch operations. In addition, banks receive hundreds of notice documents from courts, municipalities and third parties; which usually contain private and time-sensitive information about their customers. Automated document processing requires special solutions such as optical character recognition (OCR), natural language processing (NLP) and taxonomy; and modern process automation tools can utilize these solutions to provide end-to-end automation. This paper discusses how the notice documents such as account closure, payment blockage in Turkey can be automated. It also shows how automation can efficiently and effectively process the documents by providing experimental results for each document type.

İş süreci otomasyonu, sıradan ve tekrarlayan görevleri ortadan kaldırarak şirketlere yardımcı olmaktadır. Otomasyon araçları birçok sektörde kullanılmakta olup, şirketlere yüksek tam zamanlı çalışan (FTE) tasarrufu ve düşük hata oranları sağlamaktadır. Bankalar, ana bankacılık ve şube operasyonları için otomasyon araçlarını kullanmaktadırlar. Ayrıca her gün bankalara mahkemelerden, belediyelerden ve üçüncü şahıslardan yüzlerce ihbar belgesi gelir; ve bu belgeler genellikle müşteriler hakkında özel ve zamana duyarlı bilgiler içerir. Bu belgelerin otomatik işlenmesi prosedürü, optik karakter tanıma (OCR), doğal dil işleme (NLP) ve sınıflandırma gibi özel çözümler gerektirir; ve modern süreç otomasyon araçları, uçtan uca otomasyon sağlamak için bu çözümleri kullanabilir. Bu makale, Türkiye'de hesap kapatma, ödeme blokajı gibi bildirim belgelerinin nasıl otomatikleştirilebileceğini tartışmaktadır.
Belge tabanlı bankacılık süreçleri için akıllı sistem tasarımı
Keywords: Process Management and Automation; Document Understanding and Processing; Document-Based Banking Processes; Süreç Yönetimi ve Otomasyonu; Belge Anlama ve İşleme; Belge Tabanlı Bankacılık Süreçleri